-5+7q+ -5q+ -9q please help
1 answer:
For this case we must simplify the following expression
![-5 + 7q + (- 5q) + (- 9q)](https://tex.z-dn.net/?f=-5%20%2B%207q%20%2B%20%28-%205q%29%20%2B%20%28-%209q%29)
We know that, by definition:
![+ * - = -](https://tex.z-dn.net/?f=%2B%20%2A%20-%20%3D%20-)
So, rewriting the expression we have:
![-5 + 7q-5q-9q =](https://tex.z-dn.net/?f=-5%20%2B%207q-5q-9q%20%3D)
We add similar terms taking into account that:
- Equal signs are added and the same sign is placed.
- Different signs are subtracted and the major's sign is placed:
![-5 + 2q-9q =\\-5-7q](https://tex.z-dn.net/?f=-5%20%2B%202q-9q%20%3D%5C%5C-5-7q)
Answer:
![-5-7q](https://tex.z-dn.net/?f=-5-7q)
You might be interested in
Answer:
1/3
1/7
1/11
1/13
1/17
Step-by-step explanation:
mark me brainliest!!
Hello there!
the answer is 2
Hope this helps! :)
~zain
Answer:
Your answer is -5
Step-by-step explanation:
On paper;
Answer:
18=6b, b=3
Because Mary has 6 times as much as Carlos does, we put the x with 6. 18 is the number that 6x equals. 6*3=18
Answer: it has no solutions
Step-by-step explanation:
Factor then solve to find the complex solutions.